Insights Into the Environmental Impact on Genetic Structure and Larval Dispersal of Crown-of-Thorns Starfish in the South China Sea - Chen, Biao; Yu, Kefu; Yao, Qiucui; Liao, Zhiheng; Qin, Zhenjun; Yu, Xiaopeng; Wu, Qian; He, Biao (Frontiers in Marine Science, 2021)
The coral-eating crown-of-thorns starfish (COTS; Acanthaster spp.) play a major role in coral reef degradation in the Indo-Pacific region. However, the impacts of environmental factors on the phylogenetic and genetic characteristics of COTS in the northern Indo-Pacific convergence region remains unclear. We used mitochondrial DNA (mtDNA) and microsatellite markers to analyze the phylogenetic relationship, demographic history, genetic diversity and genetic structure of COTS in the South China Sea (SCS) and explored the impact of environmental factors on historical population expansion, genetic differentiation and larval dispersal. There was a clear signature of a population expansion in the SCS using the mtDNA marker. According to microsatellite loci analysis, COTS have high genetic diversity in the SCS. STRUCTURE analysis indicated that COTS in the Pacific Ocean can be divided into four subgroups: the SCS, Western Pacific, Pacific equatorial current affected zone, and Pacific insular atolls populations in the Pacific Ocean. Fst-statistical analysis revealed positive correlations between the Fst values and geographic isolation for all sampling sites. Additionally, there were no clear associations between the Fst values and chlorophyll a concentrations among coral reefs in the SCS; however, there were significant positive associations between the Fst values and particulate organic carbon (POC) concentrations within small geographic distances. These results suggest that COTS underwent historical population expansion after the Last Glacial Maximum, possibly followed by coral population expansion. The genetic structure of COTS populations may have been shaped by distinct nutrient concentrations, particularly those of POC, over small geographic distances. Moreover, ocean currents provide a potential dispersal mechanism for COTS larvae in the SCS. This study demonstrates that environmental and oceanographic factors play important roles in shaping the genetic characteristics and larval dispersal of COTS populations in the northern Indo-Pacific convergence region.